FMD molecular epizootology in Russia (phylogenetic analysis *^ß of Russian FMDV isolates) - A. V. Scherbakov (Ветеринария сегодня)
The paper sums up the results of 20-year-long FMD molecular and epizootological studies in Russia. Phylogenetic analyses of the Russian FMDV isolates are indicative of the fact that all FMD outbreaks in the Russian Federation in 1995-2014 were due to the virus introduction from other countries, mainly from China. It was demonstrated that in different years FMDV of different genetic lineages/ strains was introduced into Russia, i.e. 1995 - O/CATHAY, 2000 and 2004 - O/ME-SA/PanAsia, 2005-2006 - Asial, 2010-2011 - O/SEA/Mea-98,2012 - O/ME-SA/PanAsia, 2013 - A/ASIA/lran-05 and A/ASIA/Sea-97, 2014 - A/ASIA/Sea-97, O/ME-SA/PanAsia and O/SEA/Mea-98. The majority of the outbreaks reported in the Zabaikalsky Krai and Far East of the Russian Federation were associated with FMD panzootics having the same route of spread: from Southeast Asian countries to China and hereafter to Russia.